Integration of surface seismic waves, laboratory measurements, and downhole acoustic televiewer imaging, in geotechnical characterization: Ogden, KS - Fader, Amelia Erin (Kansas State University, 2012)
Geotechnical site characteristics are a function of the subsurface elastic moduli and the geologic structures. This study integrates borehole, surface and laboratory measurements for a geotechnical investigation that is focused on investigating shear-wave velocity (Vs) variation and its implication to geotechnical aspects of the Ogden test site in eastern Kansas. The area has a potential of seismicity due to the seismic zone associated with the Nemaha formation where earthquakes pose a moderate hazard. This study is in response to recent design standards for bridge structures require integrating comprehensive geotechnical site characterization. Furthermore, evaluation of dynamic soil properties is important for proper seismic response analysis and soil modeling programs. In this study, near surface geophysical site characterization in the form of 2D shear-wave velocity (Vs) structure that is compared with laboratory measurements of elastic moduli and earth properties at simulated in situ overburden pressure conditions and synergy with downhole Acoustic Televiewer time and amplitude logs, proved very robust “validated” workflow in site characterization for geotechnical purposes. An important component of a geotechnical site characterization is the evaluation of in-situ shear modulus, Poisson’s ratio and reliable and accurate elastic modulus ([lambda]) and shear modulus ([mu]) estimates are important in a good geotechnical site characterization. The geophysical site characterization, undertaken in this study, will complement and help in extrapolating drilling and core-based properties deduced by the geotechnical engineers interested at the test site.
Keywords: Surface wave; Acoustic televiewer; Ultrasonic laboratory measurments; Near surface site characterization; Multi channel analysis of surface waves MASW; MASW; Seismicity of Eastern Kansas; Geotechnical site characterization; Civil Engineering (0543); Geological engineering (0466); Geology (0372)